Incidence and Factors Affecting the Occurrence of Lateral Hinge Fracture After Medial Opening-Wedge High Tibial Osteotomy. Issue 10 (8th October 2021) - Lee, Sang-June; Kim, Jae-Hwa; Baek, Eugene; Ryu, Han-Seung; Han, Donghun; Choi, Wonchul
Background: Few clinical studies have reported the predictors of lateral hinge fracture (LHF) after medial opening-wedge high tibial osteotomy (MOWHTO). Purpose/Hypothesis: The purpose was to compare the incidence of LHF on plain radiographs versus computed tomography (CT) scans and to investigate the factors related to the development of LHF after MOWHTO. We hypothesized that (1) a higher LHF detection rate would be seen on CT scans versus plain radiographs and (2) LHF incidence would be related to opening gap width and hinge position. Study Design: Cohort study (diagnosis); Level of evidence, 3. Methods: A total of 97 MOWHTO cases were included. The presence and types of LHF were determined from plain radiographs and CT scans. Radiographic parameters were measured on plain radiographs taken 6 weeks postoperatively. Anterior and posterior opening gap widths, coronal and sagittal osteotomy slopes, and fibular height were calculated from CT scans. The wedge-hinge relationship and the zone of hinge position were assessed, and the patient and radiographic factors related to LHF occurrence were evaluated. Results: Seventeen LHF cases (20.5%) were detected on plain radiographs, while significantly more (37 cases; 44.6%) were found on CT scans ( P = .001). Based on Takeuchi classification, 28 LHF cases were considered type 1, 7 were type 2, and 2 were type 3. Logistic regression analysis revealed that opening gap width (odds ratio, 1.615; 95% confidence interval, 1.232-2.118; P = .001) and posterior opening gap width (odds ratio, 3.731; 95% confidence interval, 1.642-4.351; P = .008, ) differed significantly between patients with versus without LHF. Other patient and radiographic factors were not significantly related to LHF occurrence. Receiver operating characteristic curve analysis identified the opening gap width cutoff values for LHF as 11.0 mm (area under the curve, 0.81; sensitivity, 78.4%; specificity, 73.9%). Conclusion: The incidence of LHF after MOWHTO can be underestimated on plain radiographs compared with CT scans. Only large opening gap width, especially posterior gap width, was found to have a statistically significant relationship with occurrence of LHF. Therefore, special caution for possible LHF may be needed if a large correction is planned.